Reconstruction of the Lateral Collateral Ligament Using a Suture Tape Anchor for Iatrogenic Hallux Varus - Akinori Nekomoto (Hindawi Limited, 2021)
Iatrogenic hallux varus is a difficult complication of hallux valgus surgery. Although tendon transfer combined with bony correction is performed for hallux varus, tendon transfer has several disadvantages, such as the complicated nature of the procedure and the donor site morbidity. We describe the case of a 70-year-old woman with iatrogenic hallux varus treated by lateral collateral ligament (LCL) reconstruction using a suture tape anchor with bony correction. Tarsometatarsal joint arthrodesis was performed to correct the narrow intermetatarsal angle (IMA), and the varus deformity of the great toe at the metatarsophalangeal joint was corrected by anatomical reconstruction of the LCL using the suture tape anchor. One year postoperatively, the Japanese Society for Surgery of the Foot Hallux Metatarsophalangeal-Interphalangeal Scale had improved from 37 to 90 points. Radiography confirmed that the hallux valgus angle had been corrected from -24° to 4° and the IMA from 0° to 8°. Reconstruction of the LCL using suture tape anchor is an easy procedure for iatrogenic hallux varus which can achieve good stabilization.